The slippery slope effect of patient incivility: unleashing the roles of surface acting and receiving help in employees' unethical behavior and organizational citizenship behavior - Nauman, Shazia; Malik, Sania Zahra; Saleem, Farida (International journal of human resource management, 2023)
Drawing from job demands- resources model (JD-R), we examine how patient incivility (PI) is linked with nurses' unethical behavior (UB) and patient-oriented organizational citizenship behavior (POCB) through surface acting. Further, we introduced receiving help from colleagues as a boundary condition in the surface acting-unethical behavior and surface acting-POCB relationships. Two- wave multi source data gathered from 339 nurses and their colleagues working in various private hospitals of Lahore, Pakistan. We found support for the two contrasting hypotheses that patient incivility (PI) is positively associated with nurses' unethical behavior (UB) and negatively associated with patient-oriented organizational citizenship behavior (POCB) with the mediating role of surface acting. Receiving help from colleagues moderates surface acting-unethical behavior relationship such that it mitigates the negative effects of surface acting on unethical behavior whereas no moderation was found for surface acting-POCB relationship.